Does Brand Equity Affect Patient Loyalty to The Hospital? - Sinuraya, Yoridha Aulia; Girsang, Ermi; Nasution, Ali Napiah; Manalu, Putranto; Karokaro, Ulina (Al-Sihah: The Public Health Science Journal, 2021)
The rapid growth of hospitals creates conditions that force hospitals to develop business strategies to be competitive. Brand equity has a strategic role to create an advantage and distinction over other competitors. This study analyzes the effect of brand equity on brand loyalty at the hospital. The design used is cross-sectional involving 200 samples who were determined using a purposive sampling technique. The statistical test used was the t-test (α = 0.05). The results showed that the overall variable brand awareness, preference metrics, financial metrics, output metrics, competitive metrics, local marketers' perception metrics affected brand loyalty. However, partially the variables of brand awareness and perceptions of local marketers did not have a positive effect. It is recommended that the hospital improves the ease of access and affordability of facilities for patients who use vehicles, provides discounts to patients, especially general/non-insured patients who have been treated repeatedly.